In Children With Cerebral Palsy Early Diagnosis And Treatment Of Dental - Jaw Abnormalities - Shamsieva M.O; Olimov S.SH (Genius Journals, 2021)
Providing dental care to young disabled children with cerebral palsy around the world is one of the important tasks. According to experts, the number of disabled children aged 2-14 years with diseases of the central nervous system has increased from 11974.6 to 15691.2 over the past decade, there is an increase of 16 percent in cerebral palsy. Therefore, improving the treatment of dental caries in children with cerebral palsy is one of the most important problematic issues of fundamental medicine. A wide range of scientific studies on the use of EXO-and endogenous fluoride methods in measures aimed at assessing the state of caries resistance and preventing low resistance in children with various degrees of cerebral palsy is carried out in the world. In this regard, scientific research on the development of preventive measures in dentistry and improvement of treatment aimed at reducing the risk of dental caries in children with cerebral palsy is of particular importance in this regard.
Keywords: Cerebral Palsy; Dentistry; Examination; Treatment